Development of Easily Separable ZnO‐Supported Au Nanocatalyst for the Oxidative Esterification of Alcohols and Reduction of Nitroarenes. Issue 32 (29th August 2018) - Galani, Sunil M.; Giri, Arnab K.; Ghosh, Subhash C.; Panda, Asit B.
Abstract: A simple and practical protocol is described for the reduction of aromatic nitro compounds and the oxidative esterification of alcohols by using a recyclable 3D assembled porous rectangular ZnO nanoplates supported gold nanocatalysts (Au/ZnO) under mild conditions. The support 3D assembled ZnO plate was synthesized simple strategy without employing any toxic reductants or capping agents and Au was loaded through simple impregnation method. The synthesized catalyst was characterized by powder X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), electron microscopic study (TEM & SEM), diffuse reflectance spectrum (DRS). The developed catalyst showed excellent catalytic activity for both the reaction and ended with good to excellent yield, up to 97% yield for nitro reduction and 90% yield for oxidative esterification. The catalyst is recyclable for a minimum five times without any significant loss in catalytic activity. The catalytic activities are superior or sometime comparable to that of the reported catalyst. The use of a developed catalyst is beneficial for of low cost and availability of good support ZnO and advantageous with respect to that of separation, easily separable by simple filtration due to the bigger size of support ZnO. Abstract : A simple and practical protocol is described here for the reduction of aromatic nitro compounds and the oxidative esterification of alcohols by using a recyclable 3D assembled porous rectangular ZnO nanoplates supported gold nanocatalysts (Au/ZnO) under mild conditions.